Answer:
Table 3
Explanation:
The third one.
We have the function
![h(x) = \sqrt[3]{-x+2}](https://img.qammunity.org/2021/formulas/mathematics/high-school/r6unixtrcvz0dgpshn8eqrd4sabp1vx6y9.png)
Now we will insert values of x in that definition o h(x) and see if the values we obtain match the corresponding y values in the table:
![h(-6) = \sqrt[3]{-(-6)+2}= \sqrt[3]{6+2}= \sqrt[3]{8} = 2\\h(1) = \sqrt[3]{-1+2}= \sqrt[3]{1}= 1\\h(2) = \sqrt[3]{-2+2}= \sqrt[3]{0}= 0\\h(3) = \sqrt[3]{-3+2}= \sqrt[3]{1}= 1\\h(10) = \sqrt[3]{-10+2}= \sqrt[3]{-8}= -2](https://img.qammunity.org/2021/formulas/mathematics/high-school/16v0cjchnq6rf9vbr08qvnhy8n5eff0syc.png)
We can see that the values match the table 3, so the table 3 represents points on the graph of h(x)